PENGARUH MOTIVASI DAN KOMITMEN TERHADAP KINERJA GURU DENGAN SUPERVISI KEPALA SEKOLAH SEBAGAI VARIABEL INTERVANING DI SMP BHAKTI PERTIWI - Masruroh, Yuni (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
This research aims to analyze the influence of motivation and commitment on teacher performance with the supervision of the principal as an intervaning variable at SMP Bhakti Pertiwi, Probolinggo, East Java. This research approaches quantitative methods. The research location is Bhakti Pertiwi Middle School. The research population was the teaching staff at Bhakti Pertiwi Middle School, totaling 32 teachers. The results of the research show that it directly influences teacher performance at Bhakti Pertiwi Middle School. There is no significant direct effect of motivation on the supervision of the principal at Bhakti Pertiwi Middle School.